Spells, Saints, and Streghe: Witchcraft, Folk Magic, and Healing in Italy - Magliocco, Sabina (Pomegranate, 2000)
There is a rich body of ethnographic data on folk magical practices and beliefs from Italy, but for the most part Italian American Witches have not drawn from this in recreating their traditions.